Adjuvants Differentially Modulate the Immunogenicity of Lassa Virus Glycoprotein Subunits in Mice - To, Albert; Lai, Chih-Yun; Wong, Teri Ann S.; Namekar, Madhuri; Lieberman, Michael M.; Lehrer, Axel T. (Frontiers in Tropical Diseases, 2022)
Lassa Fever (LF) is an acute viral hemorrhagic fever caused by Lassa virus (LASV) that is primarily transmitted through contact with wild rodents in West Africa. Although several advanced vaccine candidates are progressing through clinical trials, some effective vaccines are virally vectored and thus require a stringent cold-chain, making distribution to rural and resource-poor areas difficult. Recombinant subunit vaccines are advantageous in this aspect as they can be thermostabilized and deployed with minimal storage and transportation requirements. However, antigen dose and adjuvant formulation must be carefully selected to ensure both the appropriate humoral and cell-mediated immune responses are elicited. In this study, we examine the immunogenicity of a two-step immunoaffinity-purified recombinant LASV glycoprotein (GP) with five clinical- and preclinical-grade adjuvants. Swiss Webster mice immunized intramuscularly with 2 or 3 doses of each vaccine formulation showed complete seroconversion and maximal GP-specific antibody response after two immunizations. Formulations with GPI-0100, LiteVax, Montanide™ ISA 51, and Montanide™ ISA 720 induced both IgG1 and IgG2 antibodies suggesting a balanced Th1/Th2 response, whereas formulation of LASV GP with Alhydrogel elicited a IgG1-dominant response. Splenocytes secreting both Th1 and Th2 cytokines i.e., IFN-γ, TNF-α, IL-2, IL-4 and IL-5, were observed from mice receiving both antigen doses formulated with ISA 720, LiteVax and GPI-0100. However, robust, multifunctional T-cells were only detected in mice receiving a higher dose of LASV GP formulated with GPI-0100. Our results emphasize the importance of careful adjuvant selection and lay the immunological basis for a recombinant subunit protein LF vaccine formulation.